210Pb dating to investigate the historical variations and identification of different sources of heavy metal pollution in sediments of the Pearl River Estuary, Southern China. (January 2020) - Ye, Zhiping; Chen, Jianyao; Gao, Lei; Liang, Zuobing; Li, Shaoheng; Li, Rui; Jin, Guangzhe; Shimizu, Yuta; Onodera, Shin-ichi; Saito, Mitsuyo; Gopalakrishnan, Gnanachandrasamy
Abstract: In this study, we investigated the historical variation, source identification, and distribution of heavy metal pollution in sediments of the Pearl River Estuary (PRE) using 210 Pb dating. Our results suggest that the heavy metal concentrations were higher in the western part of the estuary. For all heavy metals, Cd was significantly enriched in the sediments. The Pearl River Delta (PRD) has experienced rapid economic development in the past 40 years, a decreasing trend in heavy metal fluxes after 2004 was identified, which suggests a reduction in heavy metal concentrations due to the removal of heavy polluting industries and the effective control of sewage discharge. A binary mixing model reveals that the contributions of anthropogenic Pb ranged from 45.4 to 64%. Based on lead isotopic ratios ( 206/207 Pb and 208/206 Pb), it was found that geologic materials and industrial pollution were the main sources of heavy metals in the PRE sediments. Highlights: A high resolution sedimentary record of heavy metal pollution using 210 Pb dating. The heavy metal flux (except Cd) decreased after 2004. The 206 Pb/ 207 Pb vs 208 Pb/ 206 Pb ratios reflected a mixture of geological materials and industrial pollution. A binary mixing model showed that the contributions of anthropogenic Pb from 45.4 to 64%.